Adsorption of Organic Molecules in Water onto Carbon Spheres Nanostructured by Air Oxidation - Michio Inagaki; Midori Sakanishi (Adsorption Science & Technology)
Carbon spheres derived from phenol resin were subjected to mild oxidation in air at a temperature of 330–370°C leading to the development of micropores, i.e. structural modification on the nanometric scale. The relative ability of such spheres for removing Methylene Blue, Diquat and phenol from their aqueous solutions was determined by soaking them for 20 h in such solutions at concentrations of 2.0 × 10 −2 , 5.0 × 10 −5 and 1.0 × 10 −3 mol/l, respectively. It was possible to obtain a master curve for each adsorbate by shifting the experimental points corresponding to the relative removal measured on spheres oxidized at 330°C and 370°C along the logarithm of the oxidation time axis to those at 350°C. The master curve thus obtained demonstrated that the removal behaviour of the oxidized spheres was associated with the development of micropores in the adsorbent and also the relationship between oxidation time and temperature.